Effect of Zinc supplementation on haematology, oxidative stress and plasma biochemical parameters in cadmium exposed goats - V, SANKAR; MANI, VEENA; DAS, TAPAN KUMAR; KAUR, HARJIT; KEWALRAMANI, NEELAM (The Indian Journal of Animal Sciences, 2023)
The present study was designed to assess the effect of zinc supplementation on haematology, oxidative stress and plasma biochemical parameters in Cd induced lactating goats. Eighteen crossbred lactating goats were divided into three groups (Control, T1 and T2). In T1 and T2 groups, goats were given 10 ppm Cdcl2, while in T2, Zinc @100ppm was also supplemented for period of 120 days. At the end of study, blood glucose, TLC, neutrophil % and AST, ALT were increased significantly in T1 group and except glucose, Zn supplementation in T2 group showed its protective effect on TLC, neutrophil %, lymphocyte %, AST and ALT. There was significant decrease in lymphocyte %, Hb and plasma total antioxidant activity in T1 group. At 30 days, the activity of SOD was increased in T1 and T2 but thereafter activities were significantly decreased at 120 days in T1 but in T2 it was similar to control. The activity of catalase was increased on 30 and 60 days and thereafter decreased from 90 days onwards but the rate of decline was comparatively less in T2. Total immunoglobulin and lymphocyte stimulation index were significantly decreased in T1 group whereas in Zn supplemented group decline trend was less. Henceforth, it was concluded that 100 ppm Zn is helpful in reducing burden of Cd induced biochemical and oxidative stress in goats.